Development of a synchronous recording and photo-stimulating electrode in multiple brain neurons - Zhang, Qingping; Jing, Wei; Wu, Shiping; Zhu, Mengzheng; Jiang, Jingrui; Liu, Xiang; Yu, Dian; Cheng, Long; Feng, Bin; Wen, Jianbin; Xiong, Feng; Lu, Youming; et al. (Frontiers in Neuroscience, 2023)
The investigation of brain networks and neural circuits involves the crucial aspects of observing and modulating neurophysiological activity. Recently, opto-electrodes have emerged as an efficient tool for electrophysiological recording and optogenetic stimulation, which has greatly facilitated the analysis of neural coding. However, implantation and electrode weight control have posed significant challenges in achieving long-term and multi-regional brain recording and stimulation. To address this issue, we have developed a mold and custom-printed circuit board-based opto-electrode. We report successful opto-electrode placement and high-quality electrophysiological recordings from the default mode network (DMN) of the mouse brain. This novel opto-electrode facilitates synchronous recording and stimulation in multiple brain regions and holds promise for advancing future research on neural circuits and networks.